Os maracatus nação pernambucanos no contexto da globalização - Koslinski, Anna Beatriz Zanine (Universidade de São Paulo | Escola de Comunicações e Artes, 2010)
“Maracatus Nação” from Pernambuco are a current example of resistance and cultural diversity in the globalized world, emphasizing their identities by difference and legitimizing their values by tradition. The cultural manifestation is composed by a royal courtship with music and dance and it takes place mainly in poor neighborhoods communities. It origins are not certain, so, the debate among its traditions is something frequent. This article intends to analyze the context of maracatus nação in the globalized world. In order to reach that goal we will discuss the globalization itself, make a brief discussion on maracatus nação history and their current format and finally we will show in which ways the values of the globalized world interfere on the organization of such groups and their relation with the rest of the society.